Gender and National Literature : Heian Texts in the Constructions of Japanese Modernity - Yoda, Tomiko (Book collections on Project MUSE., 2004)
This work presents a new understanding of the way that classic works of Japanese literature have been received and understood within the framework of national literature studies in Japan.